1993
DOI: 10.1177/0032855593073001006
|View full text |Cite
|
Sign up to set email alerts
|

AIDS Education in U.S. Prisons: A Survey of Inmate Programs

Abstract: Prisons and other correctional environments are in many ways optimal settings for the development, delivery, and study of AIDS education and prevention programs. Prior research has shown such programs to be widespread, but little is known about their impact. This article presents findings from a recent nationwide survey of AIDS education efforts in U.S. prisons. Results (a) provide baseline information about major program variations that evaluators must take into account and (b) serve as a catalyst for discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…A review of responses to the survey questions reveals generally high levels of knowledge among the COs. A majority answering with the preferred or correct response (denoted by the asterisk) to the 20 questions measuring basic HIV/AIDS knowledge was recorded for 18 ofthe questions. This indicates high levels ofbasic knowledge about transmission ofthe disease, and these findings are consistent with the HIV/AIDS education literature (e.g., Hecht, Corman, & Miller-Rassulo, 1993;Hogan, 1994;Keeton & Swanson, 1998;Martin, Zimmerman, & Long, 1993). There are, however, troubling patterns in these Table 1 data that are also consistent with the HIV/AIDS education literature.…”
Section: -supporting
confidence: 85%
“…A review of responses to the survey questions reveals generally high levels of knowledge among the COs. A majority answering with the preferred or correct response (denoted by the asterisk) to the 20 questions measuring basic HIV/AIDS knowledge was recorded for 18 ofthe questions. This indicates high levels ofbasic knowledge about transmission ofthe disease, and these findings are consistent with the HIV/AIDS education literature (e.g., Hecht, Corman, & Miller-Rassulo, 1993;Hogan, 1994;Keeton & Swanson, 1998;Martin, Zimmerman, & Long, 1993). There are, however, troubling patterns in these Table 1 data that are also consistent with the HIV/AIDS education literature.…”
Section: -supporting
confidence: 85%
“…Without a cure, education still appears to be our best preventative measure in response to the growing number of inmates infected with HIV in correctional facilities. Few facilities, however, have provided comprehensive programming (CDC, 1996;Hammett et al, 1999) and even fewer have conducted studies to determine the effectiveness of their programs on inmates (Martin, Zimmerman, & Long, 1993). Hammet et al (1999) defined comprehensive programming to embody "instructor-led education, peer-led programs, pre and posttest counseling and multi-session prevention counseling" (p. 27).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Nearly all of the studies in this category were concerned with educational programs, whether led by peers or professionals; peer education was highlighted as particularly beneficial (Ayanwale, 2008; Boudin et al, 1999; Clark & Boudin, 1990; Collica, 2002, 2007; Martin, Zimmerman & Long, 1993; Lyons et al, 2014; Martin et al, 1995; Grinstead, Faigeles & Zack, 1997; Ross, 2006; Scott et al, 2004; West & Martin, 2000). Education programs were found to be effective in informing incarcerated men and women about HIV transmission and risk behaviors, and changing attitudes and beliefs (Ayanwale et al, 2008; Boudin et al, 1999; Grinstead, Faigeles, & Zack, 1997; Ross et al, 2006; Scott et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…These interventions had positive effects on a variety of key outcomes including HIV knowledge, intentions to change risky behaviors, perceived risk of infection, coping and social support, and HIV test rates (Ayanwale et al, 2008; Boudin et al, 1999; Bryan et al, 2006; Collica, 2007; Grinstead et al, 1997; Lyons et al, 2014; Martin et al, 1993; Martin et al, 1995; Ross et al, 2006; Scott et al, 2004; St Lawrence et al, 1997; West & Martin, 2000; West, 2001). One evaluation of a risk reduction program for women inmates suggested that communication skills were just as important to reducing HIV risk as knowledge of HIV and safe sex, as women with these skills were better able to negotiate with sex partners (St Lawrence et al, 1997).…”
Section: Discussionmentioning
confidence: 99%